Short-Term Follow-Up of the PROSTALAC Implant for Primary Total Hip Arthroplasty in Patients with an Infected Native/Total Hip - Chia, Jean; Roy, Alfred; Jackman, Emma; Inglis, Mark; Wilson, Christopher (The Journal of Hip Surgery, 2021)
Infection after a total hip replacement (THR) is a significant complication for patients and is costly for health services. The two-stage Prosthesis with Antibiotic Loaded Acrylic (PROSTALAC) procedure has been the gold standard treatment for managing THR infections. The aim of this study is to evaluate using a one-stage PROSTALAC procedure as an alternative for patients who would otherwise not be able to undergo THR surgery due to a previous hip infection.We evaluated nine cases where the PROSTALAC implant was used in the native hip. The reasons for surgery, clinical results, and complications were reviewed. An Australian Orthopaedic Association National Joint Replacement Registry data report verified that no patients were revised outside of our local center.All patients reported symptomatic relief and satisfactory function, one patient had a peri-prosthetic fracture after experiencing a fall, and one patient underwent surgery for loosening of the joint. No cases were revised to another implant or had further infection. Minimum follow-up was 2 years.Our results suggest that this implant is useful in patients with osteoarthritis of the hip with a history of previous infection or chronic infection of the native hip.
Keywords: PROSTALAC; infected; hip; arthroplasty